Association of the systemic immune-inflammation index with clinical outcomes in acute myocardial infarction patients with hypertension - Tingting Zheng; Chaodi Luo; Suining Xu; Xiyang Li; Gang Tian (BMC Immunology)
Abstract Background A new indicator of immunological and inflammatory condition, the Systemic Immunoinflammatory Index (SII), has been linked to a bad prognosis in a number of disorders. Methods Two thousand three hundred seventeen ICU patients were admitted with hypertension and acute myocardial infarction (AMI). Patients were grouped according to their baseline SII tertile number into Q1, Q2, and Q3 groups. The main outcomes were death from all causes at 30 days, 365 days, cardiogenic shock, and congestive heart failure. Results The case fatality rate increases with increasing SII. The correlation between SII and 30-day all-cause mortality [hazard ratio (HR) 1.765, 95% confidence interval (CI) 1.330–2.343 (Q3 versus Q1 group)], 365-day all-cause mortality [HR 2.713, 95% CI 2.250–3.272 (Q3 versus Q1 group), HR 1.603, 95% CI 1.312–1.959 (Q3 vs. Q1 group)], congestive heart failure [odds ratio (OR) 1.255, 95% CI 1.006–1.565 (Q2 vs. Q1 group), OR 1.565, 95% CI 1.220–2.009 (Q3 vs. Q1 group)] and cardiogenic shock [OR 1.930. 95% CI 1.271–2.974 (Q2 vs. Q1 group)] were all validated. According to subgroup analysis, individuals who had chosen to have CABG surgery had a stronger correlation between SII and a worse outcome. According to Kaplan–Meier (K-M) survival curves, patients in the Q3 group with SII had the highest rates of morbidity and death. The RCS curves demonstrated an essentially linear connection between SII and 30 days, 365 days, and congestive heart failure even after controlling for covariates. Conclusions SII was substantially correlated with 30-day all-cause mortality, 365-day all-cause mortality, in-hospital congestive heart failure, and cardiogenic shock in patients who had both hypertension and acute myocardial infarction. In individuals with acute myocardial infarction and hypertension, a greater SII would be regarded as an independent risk factor for a higher death rate.